Computation Analysis of Flow in a Round Pipe with Navier-Stokes Equations - Marpaung, Tulus Joseph Herianto; Manurung, Asima (Journal of Research in Mathematics Trends and Technology, 2022)
This research analyzes the flow in a round pipe using the Navier-Stokes equations with the aim of understanding the characteristics of flow and friction within the system. The Navier-Stokes equations are employed to describe the movement of fluid within the round pipe, taking into account the effects of viscosity and pressure on the fluid flow. Additionally, friction within the round pipe is analyzed as a consequence of the fluid flow, with the consideration of friction coefficients to depict the magnitude of frictional forces exerted on the pipe walls. Furthermore, the researchers demonstrate that friction coefficients increase with higher flow velocities and fluid viscosities. Simulation results indicate that laminar flow is the dominant condition within the round pipe under investigation. In laminar flow conditions, the boundary layers exhibit greater organization and the fluid flow is more stable. However, at higher flow velocities, a transition from laminar to turbulent flow can occur. The computational analysis presented in this study utilizes the Computational Fluid Dynamics (CFD) software COMSOL Multiphysics. This software employs robust numerical algorithms to efficiently solve the continuity, momentum, and Navier-Stokes equations. The program provides information regarding velocity profiles, pressure distributions, and other flow parameters along the round pipe. The simulation results are obtained for varying water velocities of 0.001 m/s, 0.01 m/s, 0.1 m/s, and 1 m/s. By integrating discretization methods, the continuity equation, momentum equation, Navier-Stokes equations in component form, and energy loss calculations, this study offers profound insights into flow within round pipes and its characteristics. This research provides valuable insights into flow in round pipes, the effects of friction, and the challenges in achieving convergence solutions at high water velocities.